Mesoporous material compound, preparation method thereof, photosensitive resin composition and preparation method thereof
By using a combination of mesoporous material composites and sensitizers in the photosensitive resin, the problem of slow reaction and excessive curing of photosensitive resins in high proportions of powder in SLA printing is solved, and the effects of high reactivity, high molding accuracy and high thermal stability are achieved.
Patent Information
- Application Number
- CN202411981233.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
During the SLA printing process, high-proportion powder photosensitive resins have slow reactions and insufficient cross-linking due to reflection and refraction of ultraviolet light, which affects molding accuracy and thermal stability. The prior art cannot completely solve the problems of overcuring and slow reaction by adding initiators or using light shielding agents.
The mesoporous material composites are used in combination with sensitizers to improve the cross-linking reaction in the photosensitive resin. Through the high specific surface area and high thermal conductivity of the mesoporous material, the reaction efficiency of the sensitizer is enhanced and the exothermic problem is reduced.
The reaction activity and molding accuracy of photosensitive resins containing high proportion of powder in low light are improved, the risk of overcuring in three directions of XYZ is reduced, and the thermal stability and material stiffness of molded samples are improved.
Smart Images

Figure CN119798787A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photosensitive resin materials for photocuring 3D printing, and specifically relates to a mesoporous material compound, a preparation method thereof, a photosensitive resin composition and a preparation method thereof. Background Art
[0002] Among the photocurable materials, photosensitive resins containing a high proportion of powder are often used in special fields such as electronic equipment and aviation that require high thermal stability, high wear resistance, and high rigidity. However, during the SLA printing process, due to the reflection and refraction of ultraviolet light by the high proportion of powder evenly dispersed in the photosensitive resin, the photosensitive resin reacts slowly and the cross-linking reaction is insufficient, thereby affecting the precision of the molded samples and reducing the thermal stability and material stiffness of the molded samples, especially when the energy of the given light source is insufficient. When the printing efficiency is reduced and high-energy printing is used, these 300-400nm ultraviolet lights will produce scattering effects. These weak scattered lights will induce different degrees of residual light curing at the curing interface, which will reduce the smoothness of the structure edge and shrink the hole size, affecting the molding accuracy.
[0003] Currently, the main method on the market to increase the reaction degree of photosensitive resin is to increase the initiator content in the photosensitive resin. However, a high proportion of initiators will correspondingly increase the heat release of the resin during the printing process, thereby causing microgels to form on the surface of the molded sample, affecting the printing quality. At the same time, it will cause excessive curing in the XYZ directions of the molded sample, affecting the molding accuracy. Moreover, the effect brought by a high proportion of initiators does not meet industrial requirements.
[0004] At present, light shielding agents are also used in the market to solve the problems of residual light curing and over-curing in the printing process, but the use of light shielding agents exacerbates the slow reaction of high-proportion powder photosensitive resins and reduces the mechanical properties required for molded samples. Light shielding agents such as carbon nanotubes are used to solve over-curing, but they have poor dispersion and long-term stability in 3D printing photosensitive resins.
[0005] The use of sensitizers in photosensitive resins can greatly increase their cross-linking reaction under ultraviolet light and improve printing quality. However, when the amount of sensitizer added to high-proportion powder photosensitive resins is too small, it is difficult to significantly increase the resin reaction speed; when the amount added is too large, it will also cause the reaction to release heat rapidly, which can easily cause problems such as over-curing in all directions of the molded sample and poor molding accuracy.
[0006] Therefore, the prior art needs to be improved. Summary of the invention
[0007] The present invention provides a mesoporous material compound, a preparation method thereof, a photosensitive resin composition and a preparation method thereof. The mesoporous material compound of the present invention is used in combination with a sensitizer in a photosensitive resin, which can improve the cross-linking reaction of the photosensitive resin containing a high proportion of powder in SLA printing, so that the photosensitive resin has high reactivity and high molding accuracy even under weak light, and the sample printed by the photosensitive resin containing a high proportion of powder has high thermal stability and material stiffness, and can also reduce the over-curing in the three directions of XYZ caused by the reaction exotherm, thereby improving the molding accuracy.
[0008] The present invention is achieved through the following technical solutions:
[0009] Solution 1)
[0010] The mesoporous material compound is mainly prepared from mesoporous material and carbon nanotubes in a molar ratio of 4.5-5.5:1.5-2.5. The mesoporous material is mainly prepared from urea, boric acid, water and methanol in a molar ratio of 0.15-0.3:0.01:1.2:0.5.
[0011] Specifically, the preparation method of the mesoporous material comprises the following steps: adding urea and boric acid into a ball mill, ball milling at a speed of 400-500r / min for 120-200min, then adding into a mixed liquid of methanol and water and heating to 55-70°C, keeping warm for 3-5h, heating at 100-130°C to evaporate the solvent, and obtaining a white crystalline powder; reacting at a high temperature of 800-1000°C under nitrogen protection for 2-3h, and naturally cooling to room temperature to obtain the mesoporous material.
[0012] Option 2)
[0013] The preparation method of the mesoporous material composite comprises the following steps:
[0014] First, the mesoporous material and polyvinyl pyrrolidone are added to a mixed solution of methanol and deionized water, and ultrasonically stirred for 1-2 hours to obtain a mixed solution 1;
[0015] Then, the carbon nanotubes are dispersed in a mixed solution of dimethylformamide and ethylene glycol, and ultrasonically stirred for 1-2 hours to obtain a mixed solution II;
[0016] Next, the mixture 1 and the mixture 2 are mixed and stirred for 2-3 hours, and then added into the autoclave, and deionized water is added, and then heated to 180-200° C. and kept warm for 24-36 hours;
[0017] Finally, the mixture is centrifuged, washed and dried to obtain a gray-black powder, which is the mesoporous material composite.
[0018] The mass ratio of mesoporous material, polyvinyl pyrrolidone, methanol and deionized water is 3.5-5.5:0.6-1.3:18-23:17-21;
[0019] The mass ratio of carbon nanotubes, dimethylformamide and ethylene glycol is 0.7-1.5:6-10:5-8;
[0020] The volume ratio of deionized water for dilution to mixed solution 1 is 3.5-4.5:0.5-1.5.
[0021] The mesoporous material compound of the present invention has a high specific surface area. When used in a photosensitive resin composition as a sensitizer carrier, it can increase the contact area between the sensitizer and the resin, greatly improving the reaction efficiency of the sensitizer, so reducing the amount of the sensitizer used can also achieve good results; and the mesoporous material of the present invention has high thermal conductivity, which can effectively improve the heat dissipation efficiency during the printing process, reduce the heat release problem caused by the sensitizer, and improve the precision of the molded sample; at the same time, the mesoporous material compound of the present invention has good stability in the photosensitive resin, has the characteristic of shielding light, reduces over-curing of the molded sample, and improves the molding precision.
[0022] Option 3)
[0023] The photosensitive resin composition is mainly prepared from the following components in parts by weight:
[0024] 5-10 parts of acrylic acid ester monomer;
[0025] Active diluent 5-10 parts;
[0026] Epoxy resin: 30-40 parts;
[0027] 40-50 parts of powder;
[0028] 0.5-1 part of free radical photoinitiator;
[0029] Cationic photoinitiator 3-3.5 parts;
[0030] The mesoporous material composition: 1-2 parts.
[0031] The mesoporous material composition is prepared from a mesoporous material compound and a sensitizer in a mass ratio of 60-80:20-40.
[0032] The preparation method of the mesoporous material composition comprises the following steps:
[0033] The mesoporous material composite and the sensitizer are added into toluene, ultrasonicated for 60-120 minutes at a temperature of 20-30° C., and then vacuum dried at 40-50° C. for 12-24 hours to obtain the mesoporous material composition.
[0034] The mass ratio of the mesoporous material compound to toluene is 2-4:15-20.
[0035] Dry in vacuum oven.
[0036] The boric acid, urea, methanol, carbon nanotubes, polyvinyl pyrrolidone, dimethylformamide, ethylene glycol and anhydrous ethanol are from Merrill Chemical Reagent Company.
[0037] Further, the acrylic acid ester monomer is one or any combination of two or more of propane trimethanol triacrylate, tripropylene glycol diacrylate, 1,6-hexanediol acrylate, tricyclodecane acrylate, trimethylolpropane triacrylate, bisphenol A diacrylate, diethylene glycol dimethacrylate, dipentaerythritol hexaacrylate, pentaerythritol tetraacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethyl diacrylate, bisphenol A dimethacrylate, 3(2-hydroxyethyl)isocyanuric acid triacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, 2-ethyleneoxy acrylate, and ditrimethylolpropane tetraacrylate.
[0038] Furthermore, the active diluent is one or any combination of two or more of alkylene glycidyl ether, alkylene glycidyl ether, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether, benzyl glycidyl ether, 1,6-hexanediol diglycidyl ether, o-cresyl glycidyl ether, and neopentyl glycol diglycidyl ether.
[0039] Furthermore, the epoxy resin is one or any combination of two or more of oxetane, 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate, 3,3'-(oxybismethylene)bis(3-ethyl)oxetane, 3-ethyl-3-oxetanemethanol, 1,3,5-triglycidyl-S-triazinetrione, vinylcyclohexene dioxide, diglycidyl tetrahydrophthalate, diglycidyl cyclohexane-1,2-dicarboxylate, and diglycidyl 4,5-epoxytetrahydrophthalate.
[0040] Furthermore, the powder is one or any combination of two or more of fumed silicon dioxide, nano silicon dioxide, nano aluminum oxide, nano aluminum nitride, and nano titanium dioxide.
[0041] Further, the free radical photoinitiator is one or any combination of two or more of Darocur 1173 (2-hydroxy-2-methyl-1-phenylpropanone), Irgacure 184 (1-hydroxycyclohexyl benzophenone), TPO (2,4,6-trimethylbenzoyldiphenylphosphine oxide), 907 (2-methyl-1-(4-methylthiophenyl)-2-morphinyl-1-propanone), benzoin dimethyl ether BDK, 819 (phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide), TPO-L (ethyl 2,4,6-trimethylbenzoylphosphonate), EDB (ethyl 4-dimethylamino-benzoate), OMBB (methyl o-benzoylformate), and CBP (4-chlorobenzophenone).
[0042] Further, the cationic photoinitiator is one or any combination of two or more of 4-isobutylphenyl-4'-methylphenyl iodonium hexafluorophosphate, diphenyl iodonium hexafluorophosphate, bis(4-tert-butylphenyl) iodonium hexafluorophosphate, 4,4'-dimethyldiphenyl iodonium hexafluorophosphate, phenyl(2,4,6-trimethoxyphenyl) iodonium p-toluenesulfonate, 4,4'-diacetamidophenyl iodonium hexafluorophosphate, triphenylsulfonium fluoroborate, triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, 4-tolyldiphenylsulfonium hexafluorophosphate, 4-chlorophenyldiphenylsulfonium hexafluorophosphate, 3-nitrophenyldiphenylsulfonium hexafluorophosphate, 4-acetamidophenyldiphenylsulfonium hexafluorophosphate, and (4-benzophenone)diarylsulfonium salts.
[0043] The sensitizer is one or any combination of two or more of DETX (2,4-diethylthiazolone), ITX (2-isopropylthioxanthone), benzophenone, DITX (2,4-diisopropylthioxanthone), ETX (ethylthioxanthone), 2-chlorothioxanthone, N-vinyl carbazole, 3,4-dimethoxybenzyl alcohol, 3,6-bis(dimethylamino)acridine, and 1105 (isopropylthioxanthone (2, 4 isomer mixture)).
[0044] Option 4)
[0045] The preparation method of the photosensitive resin composition mainly comprises the following steps:
[0046] The acrylate monomer, active diluent, epoxy resin, powder, free radical photoinitiator and cationic photoinitiator are mixed, and then stirred at room temperature until no particles are visible, and then the mesoporous material composition is added and stirred again until no particles are visible, thereby obtaining the photosensitive resin composition.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] The mesoporous material of the present invention has a high specific surface area. When used in a photosensitive resin composition as a sensitizer carrier, it can increase the contact area with the resin, greatly improve the reaction efficiency of the sensitizer, and reduce the amount of the sensitizer used to achieve good results. In addition, the mesoporous material of the present invention has high thermal conductivity, which can effectively improve the heat dissipation efficiency during the printing process, reduce the heat release problem caused by the sensitizer, and improve the accuracy of the molded sample. At the same time, the mesoporous material of the present invention has good stability in the photosensitive resin and has the characteristic of shielding light, which reduces over-curing of the molded sample and improves the molding accuracy.
[0049] Improve the cross-linking reaction of photosensitive resin containing a high proportion of powder in SLA printing, and make it highly reactive and have high molding accuracy even under weak light.
[0050] The samples printed by photosensitive resin containing high powder have high thermal stability and high material stiffness.
[0051] Reduce over-curing in the XYZ directions caused by reaction heat and improve molding accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a schematic diagram of the structure of mesoporous materials.
[0053] Figure 2 It is a schematic diagram of the structure of the mesoporous material composition. DETAILED DESCRIPTION
[0054] The present invention is further described below in conjunction with specific implementations and drawings.
[0055] In one embodiment, the mesoporous material composite is mainly prepared from mesoporous material and carbon nanotubes in a molar ratio of 4.5-5.5:1.5-2.5, and the mesoporous material is mainly prepared from urea, boric acid, water and methanol in a molar ratio of 0.15-0.3:0.01:1.2:0.5.
[0056] When preparing the mesoporous material, it can be prepared from urea, boric acid, water and methanol in a molar ratio of 0.15:0.01:1.2:0.5, or from urea, boric acid, water and methanol in a molar ratio of 0.3:0.01:1.2:0.5, or from urea, boric acid, water and methanol in a molar ratio of 0.2:0.01:1.2:0.5. The structural schematic diagram of the mesoporous material obtained in this embodiment is shown in FIG. Figure 1 shown.
[0057] In a preferred embodiment, the molar ratio of the mesoporous material to the carbon nanotubes is 5:2.
[0058] In one embodiment, the preparation method of the mesoporous material comprises the following steps: the preparation method of the mesoporous material comprises the following steps: adding urea and boric acid into a ball mill, ball milling at a speed of 400-500r / min for 120-200min, then adding into a mixed liquid of methanol and water and heating to 55-70°C, keeping warm for 3-5H, heating to 100-130°C to evaporate the solvent, and obtaining a white crystalline powder; reacting at a high temperature of 800-1000°C under nitrogen protection for 2-3H, and naturally cooling to room temperature to obtain the mesoporous material.
[0059] It should be pointed out here that the ball mill can be milled at a speed of 400r / min for 200min, at a speed of 500r / min for 120min, and at a speed of 450r / min for 150min. Heating the evaporating solvent at 100-130℃ will evaporate faster if the temperature is higher, and evaporate slower if the temperature is lower.
[0060] In one embodiment, the present invention provides a method for preparing a mesoporous material composite, comprising the following steps:
[0061] First, the mesoporous material and polyvinyl pyrrolidone are added to a mixed solution of methanol and deionized water, and ultrasonically stirred for 1-2 hours to obtain a mixed solution 1;
[0062] Then, the carbon nanotubes are dispersed in a mixed solution of dimethylformamide and ethylene glycol, and ultrasonically stirred for 1-2 hours to obtain a mixed solution II;
[0063] Next, the mixture 1 and the mixture 2 are mixed and stirred for 2-3 hours, then added into the autoclave, and diluted with deionized water, and then heated to 180-200° C. and kept warm for 24-36 hours;
[0064] Finally, the mixture is centrifuged, washed and dried to obtain a gray-black powder, which is the mesoporous material composite.
[0065] In one embodiment, the mass ratio of the mesoporous material, polyvinyl pyrrolidone, methanol, and deionized water is 3.5-5.5: 0.6-1.3: 18-23: 17-21;
[0066] In one embodiment, the mass ratio of carbon nanotubes, dimethylformamide, and ethylene glycol is 0.7-1.5:6-10:5-8;
[0067] In one embodiment, the volume ratio of deionized water for dilution to mixed solution 1 is 3.5-4.5:0.5-1.5.
[0068] The high-pressure reactor used in the above embodiment is a stainless steel high-pressure reactor.
[0069] In the above embodiment, the washing is performed several times with deionized water and anhydrous ethanol.
[0070] In the above embodiment, the drying is performed in a vacuum oven at 70-80° C. for 6-10 hours.
[0071] In this embodiment, the stirring time and the heating temperature fluctuate within a range to obtain the mesoporous material composite of the present invention.
[0072] The mesoporous material compound of the present invention has a high specific surface area. When used in a photosensitive resin composition as a sensitizer carrier, it can increase the contact area between the sensitizer and the resin, greatly improving the reaction efficiency of the sensitizer, so reducing the amount of the sensitizer used can also achieve good results; and the mesoporous material of the present invention has high thermal conductivity, which can effectively improve the heat dissipation efficiency during the printing process, reduce the heat release problem caused by the sensitizer, and improve the precision of the molded sample; at the same time, the mesoporous material compound of the present invention has good stability in the photosensitive resin, has the characteristic of shielding light, reduces over-curing of the molded sample, and improves the molding precision.
[0073] In one embodiment, the photosensitive resin composition of the present invention is mainly prepared from the following components in parts by weight:
[0074] 5-10 parts of acrylic acid ester monomer;
[0075] Active diluent 5-10 parts;
[0076] Epoxy resin: 30-40 parts;
[0077] 0.5-1 part of free radical photoinitiator;
[0078] Cationic photoinitiator 3-3.5 parts;
[0079] 40-50 parts of powder;
[0080] The mesoporous material composition: 1-2 parts.
[0081] In this embodiment, the corresponding photosensitive resin composition can be prepared by using the above components in amounts within the range.
[0082] The mesoporous material composition is prepared from a mesoporous material compound and a sensitizer in a mass ratio of 60-80:20-40.
[0083] It should be noted that the mesoporous material composition of the present invention can be prepared from a mesoporous material compound and a sensitizer in a mass ratio of 60:40, or a mesoporous material compound and a sensitizer in a mass ratio of 80:20, or a mesoporous material compound and a sensitizer in a mass ratio of 70:30. Of course, it can also be prepared from any other ratio of a mesoporous material compound and a sensitizer within a certain range.
[0084] The structural formula of the mesoporous material composition of the present invention is as follows Figure 2 shown.
[0085] The method for preparing the mesoporous material composition comprises the following steps:
[0086] The mesoporous material composite and the sensitizer are added into toluene, ultrasonicated for 60-120 minutes at a temperature of 20-30° C., and then vacuum dried at 40-50° C. for 12-24 hours to obtain the mesoporous material composition.
[0087] The mass ratio of the mesoporous material compound to toluene is 2-4:15-20. This ratio can well mix the mesoporous material compound and the sensitizer evenly.
[0088] Dry in vacuum oven.
[0089] The boric acid, urea, methanol, carbon nanotubes, polyvinyl pyrrolidone, dimethylformamide, ethylene glycol and anhydrous ethanol are from Merrill Chemical Reagent Company.
[0090] In one embodiment, the acrylic acid ester monomer is one or any combination of two or more of propane trimethanol triacrylate, tripropylene glycol diacrylate, 1,6-hexanediol acrylate, tricyclodecane acrylate, trimethylolpropane triacrylate, bisphenol A diacrylate, diethylene glycol dimethacrylate, dipentaerythritol hexaacrylate, pentaerythritol tetraacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethyl diacrylate, bisphenol A dimethacrylate, 3(2-hydroxyethyl)isocyanuric acid triacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, 2-ethyleneoxy acrylate, and ditrimethylolpropane tetraacrylate.
[0091] In one embodiment, the active diluent is one or any combination of two or more of alkylene glycidyl ether, alkylene glycidyl ether, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether, benzyl glycidyl ether, 1,6-hexanediol diglycidyl ether, o-cresyl glycidyl ether, and neopentyl glycol diglycidyl ether.
[0092] In one embodiment, the epoxy resin is one or any combination of two or more of oxetane, 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate, 3,3'-(oxybismethylene)bis(3-ethyl)oxetane, 3-ethyl-3-oxetanemethanol, 1,3,5-triglycidyl-S-triazinetrione, vinylcyclohexene dioxide, diglycidyl tetrahydrophthalate, diglycidyl cyclohexane-1,2-dicarboxylate, and diglycidyl 4,5-epoxytetrahydrophthalate.
[0093] In one embodiment, the powder is one or any combination of two or more of fumed silica, nano silicon dioxide, nano alumina, nano aluminum nitride, and nano titanium dioxide.
[0094] In one embodiment, the free radical photoinitiator is one or any combination of two or more of Darocur 1173 (2-hydroxy-2-methyl-1-phenylpropanone), Irgacure 184 (1-hydroxycyclohexyl benzophenone), TPO (2,4,6-trimethylbenzoyldiphenylphosphine oxide), 907 (2-methyl-1-(4-methylthiophenyl)-2-morphinyl-1-propanone), benzoin dimethyl ether BDK, 819 (phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide), TPO-L (ethyl 2,4,6-trimethylbenzoylphosphonate), EDB (ethyl 4-dimethylamino-benzoate), OMBB (methyl o-benzoylformate), and CBP (4-chlorobenzophenone).
[0095] In one embodiment, the cationic photoinitiator is one or any combination of two or more of 4-isobutylphenyl-4'-methylphenyl iodonium hexafluorophosphate, diphenyl iodonium hexafluorophosphate, bis(4-tert-butylphenyl) iodonium hexafluorophosphate, 4,4'-dimethyldiphenyl iodonium hexafluorophosphate, phenyl(2,4,6-trimethoxyphenyl) iodonium p-toluenesulfonate, 4,4'-diacetamidophenyl iodonium hexafluorophosphate, triphenylsulfonium fluoroborate, triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, 4-tolyldiphenylsulfonium hexafluorophosphate, 4-chlorophenyldiphenylsulfonium hexafluorophosphate, 3-nitrophenyldiphenylsulfonium hexafluorophosphate, 4-acetamidophenyldiphenylsulfonium hexafluorophosphate, and (4-benzophenone)diarylsulfonium salts.
[0096] In one embodiment, the sensitizer is one or any combination of two or more of DETX (2,4-diethylthiazolone), ITX (2-isopropylthioxanthone), benzophenone, DITX (2,4-diisopropylthioxanthone), ETX (ethylthioxanthone), 2-chlorothioxanthone, N-vinyl carbazole, 3,4-dimethoxybenzyl alcohol, 3,6-bis(dimethylamino)acridine, and 1105 (isopropylthioxanthone (2, 4 isomeric mixture)).
[0097] In order to further illustrate the effects of the present invention, specific examples 1-14 and comparative examples 1-4 are provided, but are not limited to the following examples.
[0098] The preparation methods of the photosensitive resin compositions of Examples 1-12 mainly include the following steps:
[0099] Mix the acrylic monomer, active diluent, epoxy resin, powder, free radical photoinitiator and cationic photoinitiator shown in Table 1, and then stir at room temperature until no particles are visible, then add the mesoporous material composition, and stir again until no particles are visible, to obtain the photosensitive resin composition.
[0100] The preparation method of the photosensitive resin composition of Control Examples 1-4 comprises the following steps: mixing the acrylic monomer, reactive diluent, epoxy resin, powder, free radical photoinitiator and cationic photoinitiator as shown in Table 1, and then stirring at room temperature until no particles are visible.
[0101] The mesoporous material compositions used in Examples 1-12 are all prepared from a mesoporous material compound and a sensitizer (DETX) in a mass ratio of 70:30.
[0102] The preparation method of the mesoporous material composition comprises the following steps:
[0103] The mesoporous material composite and the sensitizer are added into toluene, ultrasonicated for 120 minutes at 20° C., and then vacuum dried at 40° C. for 24 hours to obtain the mesoporous material composition.
[0104] The mass ratio of the mesoporous material compound to toluene is 2:15.
[0105] The mesoporous material composite used in Examples 1-12 is prepared from a mesoporous material and carbon nanotubes at a molar ratio of 5:2. The preparation method comprises the following steps:
[0106] Firstly, the mesoporous material and polyvinyl pyrrolidone are added into a mixed solution of methanol and deionized water, and ultrasonically stirred for 1 hour to obtain a mixed solution 1;
[0107] Then, the carbon nanotubes were dispersed in a mixed solution of dimethylformamide and ethylene glycol, and ultrasonically stirred for 1 hour to obtain a mixed solution II;
[0108] Next, the mixture 1 and the mixture 2 were mixed and stirred for 2 h, then added into the autoclave, and diluted with deionized water, and then heated to 180°C and kept warm for 36 h;
[0109] Finally, the mixture is centrifuged, washed and dried to obtain a gray-black powder, which is the mesoporous material composite.
[0110] The mass or volume ratio of the mesoporous material, polyvinyl pyrrolidone, methanol, and deionized water is 4.6:1.2:21:19.
[0111] The mass or volume ratio of carbon nanotubes, dimethylformamide and ethylene glycol is 1.1:8:6.5.
[0112] The molar ratio of the mesoporous material to the carbon nanotubes is 5:2.
[0113] The mass ratio or volume ratio of deionized water for dilution to mixed solution 1 is 4:1.
[0114] Embodiment 13
[0115] The difference between Example 13 and Example 12 is that the mesoporous material compositions of this example are all prepared by a mesoporous material compound and a sensitizer (DETX) in a mass ratio of 60:40.
[0116] The preparation method of the mesoporous material composition comprises the following steps:
[0117] The mesoporous material composite and the sensitizer are added to toluene, ultrasonicated at 25° C. for 100 minutes, and then vacuum dried at 45° C. for 20 hours to obtain the mesoporous material composition.
[0118] The mass ratio of the mesoporous material compound to toluene is 4:20.
[0119] Embodiment 14
[0120] The difference between Example 13 and Example 12 is that the mesoporous material compositions of this example are all prepared by a mesoporous material compound and a sensitizer (DETX) in a mass ratio of 80:20.
[0121] The preparation method of the mesoporous material composition comprises the following steps:
[0122] The mesoporous material composite and the sensitizer are added into toluene, ultrasonicated at 30° C. for 60 minutes, and then vacuum dried at 50° C. for 12 hours to obtain the mesoporous material composition.
[0123] The mass ratio of the mesoporous material compound to toluene is 3:17.
[0124] Embodiment 15
[0125] The difference from Example 12 is that the mesoporous material composite of this example is mainly prepared from mesoporous material and carbon nanotubes in a molar ratio of 4.5:2.5, and the preparation method comprises the following steps:
[0126] First, the mesoporous material and polyvinyl pyrrolidone are added to a mixed solution of methanol and deionized water, and ultrasonically stirred for 1.2 hours to obtain a mixed solution 1;
[0127] Then, the carbon nanotubes were dispersed in a mixed solution of dimethylformamide and ethylene glycol, and ultrasonically stirred for 1.2 h to obtain a mixed solution II;
[0128] Next, the mixture 1 and the mixture 2 were mixed and stirred for 2.5 h, then added into the autoclave, diluted with deionized water, and then heated to 190° C. and kept warm for 30 h;
[0129] Finally, centrifugal separation, washing and drying are performed to obtain gray-black powder, which is the mesoporous material composite.
[0130] The mass ratio of mesoporous material, polyvinyl pyrrolidone, methanol, and deionized water is 3.5:1.3:23:21;
[0131] The mass ratio of carbon nanotubes, dimethylformamide, and ethylene glycol is 0.7:10:8;
[0132] The molar ratio of the mesoporous material to the carbon nanotubes is 4.5:2.5.
[0133] The volume ratio of deionized water and mixed solution 1 for dilution is 3.5:1.5.
[0134] Example 16
[0135] The difference from Example 12 is that the mesoporous material composite of this example is mainly prepared from mesoporous material and carbon nanotubes in a molar ratio of 5.5:1.5, and the preparation method includes the following steps:
[0136] First, the mesoporous material and polyvinyl pyrrolidone are added to a mixed solution of methanol and deionized water, and ultrasonically stirred for 1-2 hours to obtain a mixed solution 1;
[0137] Then, the carbon nanotubes are dispersed in a mixed solution of dimethylformamide and ethylene glycol, and ultrasonically stirred for 1-2 hours to obtain a mixed solution II;
[0138] Next, the mixture 1 and the mixture 2 were mixed and stirred for 3 h, then added into the autoclave, diluted with deionized water, and then heated to 200 °C and kept warm for 24 h;
[0139] Finally, centrifugal separation, washing and drying are performed to obtain gray-black powder, which is the mesoporous material composite.
[0140] The mass ratio of mesoporous material, polyvinyl pyrrolidone, methanol, and deionized water is 5.5:0.6:18:17;
[0141] The mass ratio of carbon nanotubes, dimethylformamide, and ethylene glycol is 1.5:6:5;
[0142] The molar ratio of the mesoporous material to the carbon nanotubes is 5.5:1.5.
[0143] The volume ratio of deionized water and mixed solution 1 for dilution is 4.5:0.5.
[0144] Embodiment 17
[0145] The difference from Example 12 is that the formulation of the photosensitive resin composition of this example is different.
[0146] Embodiment 18
[0147] The difference from Example 12 is that the formulation of the photosensitive tree composition in this example is different.
[0148] In order to facilitate the testing of the relevant properties of the resin compositions obtained by the above-mentioned embodiments and control examples, a model was established by an SLA printer to print out samples, wherein Table 2 is the performance test results of the samples printed out by the SLA printer using low-power printing (600mw) of the photosensitive resin compositions of each embodiment and control example, and Table 3 is the performance test results of the samples printed out by the SLA printer using high-power printing (1200mw) of the photosensitive resin compositions of each embodiment and control example. The printed samples were post-cured in a UV curing box for 30 minutes, and cured in a heating oven at a gradient temperature of 80°C / 2H-120°C / 2H-160°C / 2H, and the relevant mechanical properties, heat resistance, and dimensional accuracy of the samples were tested.
[0149] Table 1 The dosage of each component of Examples 1-14 and Comparative Examples 1-4
[0150]
[0151]
[0152] Table 2 Properties of samples of resin compositions prepared in various embodiments and comparative examples using low power printing
[0153]
[0154] Table 2 Properties of samples of resin compositions prepared in various embodiments and comparative examples using high power printing
[0155]
[0156] The comparative data in the above table show that, compared with control examples 1-4, the products printed by the photosensitive resin composition for improving SLA printing accuracy prepared by the present invention have obvious advantages in strength, stiffness, heat resistance stability and dimensional accuracy. Note: The bending strength in the table is usually used to indicate the strength of the material; the bending modulus is usually used to indicate the stiffness of the material; HDT is usually used to indicate the heat resistance stability of the material; the degree of over-curing in the XY direction is usually used to indicate the dimensional accuracy of the material in the XY direction; the degree of over-curing in the Z direction is usually used to indicate the dimensional accuracy of the material in the Z direction.
[0157] The present invention is not limited to the above embodiments, and all improvements made based on the principles of the present invention are within the protection scope of the present invention.
Claims
1. A mesoporous material compound, characterized in that: It is mainly made of mesoporous materials and carbon nanotubes with a molar ratio of 4.5-5.5:1.5-2.
5. The mesoporous material is mainly prepared from urea, boric acid, water and methanol in a molar ratio of 0.15-0.3:0.01:1.2:0.
5.
2. The mesoporous material composite according to claim 1, characterized in that: The preparation method of the mesoporous material comprises the following steps: adding urea and boric acid into a ball mill, ball milling at a rotation speed of 400-500 r / min for 120-200 min, then adding into a mixed liquid of methanol and water, heating to 55-70° C., keeping the temperature for 3-5 hours, heating to 100-130° C. to evaporate the solvent, and obtaining a white crystalline powder; then heating the white crystalline powder at a high temperature of 800-1000° C. under nitrogen protection, reacting for 2-3 hours, and naturally cooling to room temperature to obtain the mesoporous material.
3. The method for preparing the mesoporous material composite according to claim 1 or 2, characterized in that: The steps include: First, the mesoporous material and polyvinyl pyrrolidone are added to a mixed solution of methanol and deionized water, and ultrasonically stirred for 1-2 hours to obtain a mixed solution 1; Then, the carbon nanotubes are dispersed in a mixed solution of dimethylformamide and ethylene glycol, and ultrasonically stirred for 1-2 hours to obtain a mixed solution II; Next, the mixture 1 and the mixture 2 are mixed and stirred for 2-3 hours, then added into the autoclave, and diluted with deionized water, and then heated to 180-200° C. and kept warm for 24-36 hours; Finally, centrifugal separation, washing and drying are performed to obtain gray-black powder, which is the mesoporous material composite.
4. The method for preparing the mesoporous material composite according to claim 3, characterized in that: The mass ratio of mesoporous material, polyvinyl pyrrolidone, methanol and deionized water is 3.5-5.5:0.6-1.3:18-23:17-21; The mass ratio of carbon nanotubes, dimethylformamide and ethylene glycol is 0.7-1.5:6-10:5-8; The volume ratio of deionized water for dilution to mixed solution 1 is 3.5-4.5:0.5-1.
5.
5. A photosensitive resin composition, characterized in that: It is mainly prepared from the following components by weight: 5-10 parts of acrylic acid ester monomer; Active diluent 5-10 parts; Epoxy resin 30-40 parts; 0.5-1 part of free radical photoinitiator; Cationic photoinitiator 3-3.5 parts; 40-50 parts of powder; 1-2 parts of mesoporous material composition; The mesoporous material composition is prepared from the mesoporous material compound according to claim 1 or 2 and a sensitizer in a mass ratio of 60-80:20-40.
6. The photosensitive resin composition according to claim 5, characterized in that: The method for preparing the mesoporous material composition comprises the following steps: The mesoporous material composite and the sensitizer are added into toluene, ultrasonicated for 60-120 minutes at a temperature of 20-30° C., and then vacuum dried at 40-50° C. for 12-24 hours to obtain the mesoporous material composition.
7. The photosensitive resin composition according to claim 5, characterized in that: The acrylic ester monomer is one or any combination of two or more of propane trimethanol triacrylate, tripropylene glycol diacrylate, 1,6-hexanediol acrylate, tricyclodecane acrylate, trimethylolpropane triacrylate, bisphenol A diacrylate, diethylene glycol dimethacrylate, dipentaerythritol hexaacrylate, pentaerythritol tetraacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethyl diacrylate, bisphenol A dimethacrylate, 3 (2-hydroxyethyl) isocyanuric acid triacrylate, 2-butyl-2-ethyl-1,3-propylene glycol diacrylate, 2-ethyleneoxy acrylate, and ditrimethylolpropane tetraacrylate.
8. The photosensitive resin composition according to claim 5, characterized in that: The active diluent is one or any combination of two or more of alkylene glycidyl ether, alkylene glycidyl ether, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether, benzyl glycidyl ether, 1,6-hexanediol diglycidyl ether, o-cresyl glycidyl ether and neopentyl glycol diglycidyl ether.
9. The photosensitive resin composition according to claim 5, characterized in that: The epoxy resin is one or any combination of two or more of oxetane, 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate, 3,3'-(oxybismethylene)bis(3-ethyl)oxetane, 3-ethyl-3-oxetanemethanol, 1,3,5-triglycidyl-S-triazinetrione, vinylcyclohexene dioxide, diglycidyl tetrahydrophthalate, diglycidyl cyclohexane-1,2-dicarboxylate, and diglycidyl 4,5-epoxytetrahydrophthalate; The powder is one or any combination of two or more of fumed silicon dioxide, nano silicon dioxide, nano aluminum oxide, nano aluminum nitride, and nano titanium dioxide; The free radical photoinitiator is one or any combination of two or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl benzophenone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morphinyl-1-propanone, benzoin dimethyl ether BDK, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl 2,4,6-trimethylbenzoylphosphonate, ethyl 4-dimethylamino-benzoate, methyl o-benzoylformate, and 4-chlorobenzophenone; The cationic photoinitiator is one or any combination of two or more of 4-isobutylphenyl-4'-methylphenyl iodonium hexafluorophosphate, diphenyl iodonium hexafluorophosphate, bis(4-tert-butylphenyl) iodonium hexafluorophosphate, 4,4'-dimethyldiphenyl iodonium hexafluorophosphate, phenyl(2,4,6-trimethoxyphenyl) iodonium p-toluenesulfonate, 4,4'-diacetamidophenyl iodonium hexafluorophosphate, triphenylsulfonium fluoroborate, triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, 4-tolyldiphenylsulfonium hexafluorophosphate, 4-chlorophenyldiphenylsulfonium hexafluorophosphate, 3-nitrophenyldiphenylsulfonium hexafluorophosphate, 4-acetamidophenyldiphenylsulfonium hexafluorophosphate, and (4-benzophenone) diarylsulfonium salts; The sensitizer is one of 2,4-diethylthiazolone, 2-isopropylthioxanthone, benzophenone, 2,4-diisopropylthioxanthone, ethylthioxanthone, 2-chlorothioxanthone, N-vinyl carbazole, 3,4-dimethoxybenzyl alcohol, 3,6-di(dimethylamino)acridine, and isopropylthioxanthone (2, 4 isomer mixture) or any combination of two or more thereof.
10. The method for preparing the photosensitive resin composition according to claim 5, characterized in that: The main steps are as follows: The acrylate monomer, active diluent, epoxy resin, powder, free radical photoinitiator and cationic photoinitiator are mixed, and then stirred at room temperature until no particles are visible, and then the mesoporous material composition is added and stirred again until no particles are visible, thereby obtaining the photosensitive resin composition.